Crime, insecurity and corruption: Considering the growth of urban private security. (April 2018) - Garmany, Jeff; Galdeano, Ana Paula
We call into question the growing presence of private security companies (PSCs) in cities throughout the world. Though PSCs have grown enormously in recent decades, there exist few academic analyses to consider their broad-reaching effects. Researchers still have much to understand about the relationships between PSCs and changing patterns of urban development, governance and public security. PSCs are prevalent in both the Global North and South, yet their presence is perhaps most intense in emerging countries, where social inequality is high and public security is tenuous. As such, in this article we draw on specific examples from the city of São Paulo, Brazil, where demand is soaring for private security and PSCs operate in complicated networks between the state, private capital and organised crime. Our analysis draws attention to the paradoxes of urban private security, beginning with the fact that public insecurity is in fact good for PSC business. By reflecting on existing published resources – and making connections across several disciplines – our goals in this article are threefold: (1) to highlight the need for more research on PSCs in urban settings; (2) to draw attention to the ways private security is changing urban space, and; (3) to suggest that the growth of PSCs, rather than being representative of increased public security, may in some cases coincide with rising levels of urban crime and insecurity.